2007
DOI: 10.1111/j.1360-0443.2007.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Crack cocaine trajectories among users in a midwestern American city

Abstract: Crack cocaine use that persists for a decade or longer may well be the norm for a large proportion of people who have experience with the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 52 publications
(61 reference statements)
2
39
0
2
Order By: Relevance
“…Findings from large scale epidemiological studies have shown that more than 30 percent of people who have smoked crack experienced symptoms of cocaine dependence within 2 years of initiating use (Chen and Anthony, 2004). Results from our crack trajectories study revealed 33% of users met current cocaine dependence criteria (Falck et al, 2007). While data from these recent studies suggest that many people who move beyond experimentation with crack will develop cocaine dependency, they also suggest that some people who use the drug can do so over long periods of time without becoming addicted to it.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Findings from large scale epidemiological studies have shown that more than 30 percent of people who have smoked crack experienced symptoms of cocaine dependence within 2 years of initiating use (Chen and Anthony, 2004). Results from our crack trajectories study revealed 33% of users met current cocaine dependence criteria (Falck et al, 2007). While data from these recent studies suggest that many people who move beyond experimentation with crack will develop cocaine dependency, they also suggest that some people who use the drug can do so over long periods of time without becoming addicted to it.…”
Section: Introductionmentioning
confidence: 73%
“…There were no statistically significant differences between those in the continued use group who completed the final interview and those who did not return for the final interview in terms of age, race/ethnicity, gender, or educational status. Additional information on the follow-up process and rates is available elsewhere (Falck et al, 2007).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…O contexto de vulnerabilidade que permeia a vida dos usuários de crack pode ser exacerbado pelo uso compulsivo dessa substância, fazendo com que muitos se exponham a outras situações agravantes para a saúde. Nesse sentido, no Brasil e no exterior, alguns estudos realizados com usuários de crack encontraram perfi s bastante similares, caracterizados principalmente por maioria do sexo masculino, jovens e de baixo nível educacional (Falck, Wang, & Carlson, 2007;Laranjeira & Ribeiro, 2010;Pulcherio, Stolf, Pettenon, Fensterseifer, & Kessler, 2010).…”
Section: Perfi L De Los Consumidores De Crack En La Ciudad De Santos unclassified
“…This large four-city cohort, while broader than single-community samples, 33 was not nationally representative. However, there has been no trajectory analysis of these drugs in a national sample.…”
Section: Limitationsmentioning
confidence: 99%